Case Report: The use of a 3D printed alignment guide system for correction of a delayed union/nonunion/malunion femoral fracture in a dog - Scortea, Radu; Muresan, Cosmin; Krauß, Maximiljan (Frontiers in Veterinary Science, 2025)
A two-year-old neutered male mixed-breed dog was presented with a history of chronic lameness of the right pelvic limb. Physical examination and diagnostic imaging report revealed a delayed union with suspected progression toward nonunion/malunion of the femur. Further assessment showed the presence of a multiplanar deformity with a distal femoral valgus, a caudomedial translation of 26 mm, a femoral torsion angle of 35° compared to 21° to the left, and an excessive limb shortening of 34% in the frontal plane/ 31% in the sagittal plane. A 3D-printed alignment guide (3DPAG) was designed, printed, and successfully used to reduce the delayed union/nonunion fracture. The pre-contoured LCP plate, secured with seven screws, provided stable fracture fixation. The 3DPAG contributed significantly to achieving accurate alignment and implant placement.